The Impact of Production Techniques on Pore Size Distribution in High-Strength Foam Concrete - Slava Markin; Genadijs Sahmenko; Aleksandrs Korjakins; Viktor Mechtcherine (Infrastructures)
This study examined the impact of various foam concrete production techniques on pore size distribution and its water absorption properties. Techniques such as the use of a cavitation disintegrator and a turbulent mixer were employed to produce foam concrete. Six foam concrete compositions, with dry densities ranging from 820 to 1480 kg/m3 and compressive strength up to 47 MPa, were prepared. A novel method for digital image correlation was applied to analyse the pore size distribution within the foam concrete specimens. The manufactured foam concrete specimens’ porosity and water absorption indices were determined. The experimental results, including compression strength and water absorption, indicated that the production technique significantly affects the pore size distribution in foam concrete, impacting its mechanical and durability properties. Compressive strength was assessed at curing intervals of 7, 28, and 180 days. Cavitation technology was found to promote the formation of a finer porous structure in foam concrete, resulting in enhanced strength properties.